HYPERCYCLICITY AND SUPERCYCLICITYFOR SOME CLASSES OF OPERATORS - Ahmed, Buthainah A; Al-Janaby, Hiba F (Al-Nahrain Journal of Science, 2009)
In this paper,we prove that, if is the quotient of a decomposable on a separable Banach space (M–hyponormal operator on a real Hilbert space), then is hypercyclic operators. We also show that these classes of operators are supercyclic operators.